Development of iron–ascorbic acid microcapsules using Brewer's spent grain arabinoxylans as wall materials and study of their application as fortifiers in extruded corn products - Heinen, Gabriel Dario (2025)
Fortification is a sustainable long-term strategy to address iron deficiency and anemia. Microencapsulation could be used to protect iron from interaction with other food components and increase its bioaccessibility. This study aimed to develop iron microcapsules using arabinoxylans (AXs) extracted from Brewer´s spent grain as an encapsulating material and ascorbic acid (AA) as an absorption promoter for use as fortifiers in extruded corn products. Two levels of iron were studied (12.8 and 24.4 mg Fe per g solids), with AA (in an AA[thin space (1/6-em)]:[thin space (1/6-em)]Fe molar ratio of 1.5[thin space (1/6-em)]:[thin space (1/6-em)]1), keeping the iron[thin space (1/6-em)]:[thin space (1/6-em)]AX ratio constant at 1[thin space (1/6-em)]:[thin space (1/6-em)]20. The microcapsules were produced through spray drying. Subsequently, corn extrudates fortified with iron microcapsules or ferrous sulfate were produced, and the stability of the fortified samples stored at room temperature for one year was studied. Iron bioaccessibility from microcapsules and extruded corn products was determined after in vitro gastrointestinal digestion. Results indicated that ascorbic acid was partially protected from oxidation during the spray drying process (∼53%). This allowed the microencapsulated iron to remain bioaccessible under the conditions of the gastrointestinal environment (∼20%). The extruded corn product with the addition of microcapsules presented good iron bioaccessibility, which was higher than that of ferrous sulfate (∼18 vs. 12%). However, the wall material failed to protect ascorbic acid from degradation during the thermal extrusion process. The products fortified with the microcapsules with the lowest iron level were more stable than the product fortified with ferrous sulfate. It was feasible to obtain an iron fortifier with good bioaccessibility using AXs as encapsulating agents.